GAMBARAN TINGKAT PENGETAHUAN TENTANG KARANG GIGI ANGGOTA KARANG TARUNA DESA IBUN MAJALAYA KABUPATEN BANDUNG (Jurnal Kesehatan Siliwangi, 2021)
Dental and oral health is a very important part of overall health. Dental and oral health also plays a very important role in improving one's quality of life. Dental and oral health maintenance is an effort to improve dental and oral health because it can prevent diseases in the oral cavity. The lack of awareness of the importance of maintaining dental and oral health is evident from the knowledge possessed. Lack of knowledge about the importance of maintaining dental and oral health leads to the onset of neglect of dental and oral hygiene. Obtained Level of Knowledge About Tartar Members of coral cadet  at Bandung Regency The type of research used in this study is descriptive, i.e. research conducted to create an objective picture or description of the situation. The circumstances that will be described in the study on The Level of Knowledge About Tartar Members of Bandung Regency. The results obtained from filling out dental and oral health questionnaires are often the umpteenth priority for some people. Dental and oral health maintenance is an effort to improve dental and oral health because it can prevent diseases in the oral cavity. The lack of awareness of the importance of maintaining dental and oral health is evident from the knowledge possessed. Lack of knowledge about the importance of maintaining dental and oral health leads to the onset of neglect of dental and oral hygiene. The majority of 15 people (50%) of respondents have good criteria.